2019
DOI: 10.7717/peerj.7896
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences on medical students’ attitudes toward patient-centred care: a cross-sectional survey conducted in Heilongjiang, China

Abstract: ObjectivesAssessing medical students’ attitudes toward patient-centred care is essential to bettering medical education. Based on doctor-patient relationships and the medical system in China, it is important to explore the impact of gender differences and other background factors on patient-centred attitudes and to provide references for medical education reform.MethodsA cross-sectional study was conducted on fourth-year medical undergraduate students from November 2017 to March 2018 in Heilongjiang Province, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 31 publications
(54 reference statements)
3
25
1
3
Order By: Relevance
“…The observed lower score of sharing subscale among Chinese physicians in primary care may contribute to environmental factors, such as Chinese cultural values, local health system [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed lower score of sharing subscale among Chinese physicians in primary care may contribute to environmental factors, such as Chinese cultural values, local health system [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the practice of a more autonomist style, a study that assessed psychiatrists' sharing-based decision behaviours reported higher scores for women [65]. Likewise, in more recent studies, female physicians [23,66] and medical students [66,67] had signi cantly more patient-centred attitudes (understood as share of power, control, and information; respect for patients' feelings, expectations, and preferences taking these factors into account in medical decision-making [68]), suggesting that gender-stereotyped communication is established through the attitudes of medical students and seems to persist among practicing physicians [66]. These differences are even more important in that they lead to corresponding differences in patients' behaviour towards physicians.…”
Section: Discussionmentioning
confidence: 81%
“…In line with the practice of a more autonomist style, a study that assessed psychiatrists' sharing-based decision behaviours reported higher scores for women [62]. Likewise, in more recent studies, female physicians [23,63] and medical students [63,64] had signi cantly more patient-centred attitudes (understood as share of power, control, and information; respect for patients' feelings, expectations, and preferences taking these factors into account in medical decision-making [65]), suggesting that gender-stereotyped communication is established through the attitudes of medical students and seems to persist among practicing physicians [63]. These differences are even more important in that they lead to corresponding differences in patients' behaviour towards physicians.…”
Section: Discussionmentioning
confidence: 81%